Efficacy of aerosol reduction measures for dental aerosol generating procedures. Issue 5 (4th May 2022) - He, Zixin; Gao, Qiman; Henley, Anna; Der Khatchadourian, Zovinar; Somerville, Wendy; Wiseman, Michael; Mongeau, Luc; Tamimi, Faleh
Abstract: Aerosol particles generated by dental procedures could facilitate the transmission of infectious diseases and contain carcinogen particles. Such particles can penetrate common surgical masks and reach the lungs, leading to increased risk for dental care professionals. However, the risk of inhaling contaminated aerosol and the effectiveness of aerosol reduction measures in dental offices remain unclear. The present study aimed to quantify aerosols produced by drilling and scaling procedures and to evaluate present recommendations for aerosol reduction. The concentration of aerosol particles released from the mock scaling and drilling procedures performed on a dental mannequin were measured using a TSI Optical Particle Sizer (OPS 3330) during 15-min sessions carried out in a single-patient examination room. Using the mock drilling procedure as the aerosol source, the aerosol reduction performance of two types of high-volume evacuators (HVEs) and a commercial off-the-shelf air purifier was evaluated in a simulated clinical setting. The use of either HVEs or the air purifier individually reduced the aerosol accumulated over the course of a 15-min drilling procedure at a reduction rate of 94.8 to 97.6%. Using both measures simultaneously raised the reduction rate to 99.6%. The results show that existing HVEs can effectively reduce aerosol concentration generated by a drilling procedure and can be further improved by using an air purifier. Following current regulatory guidelines can ensure a low risk of inhaling contaminated aerosol for dentists, assistants, and patients. Copyright © 2022 American Association for Aerosol Research